Prescribility of generic microemulsion Cyclosporine A in heart transplant patients - Manrique,Ricardo (2003)
OBJECT: This paper aims to define the prescribility (therapeutic efficacy and bio-safety) of generic microemulsion Cyclosporin (Sigmasporin Microral®). METHOD: Casuistic: Twenty heart transplantation patients, 13 males and 7 females, with a mean age of 49.6 years, began immunosuppression treatment with generic microemulsion cyclosporin (Sigmasporin Microral®). They underwent clinical and laboratory evaluation during a minimum of three months. Procedures included clinic evaluation with electro and echocardiogram, endomyocardial biopsy, routine biochemical and hematological tests. RESULTS: The mean follow-up was 10 months with a maximum of 16 months. A total of 151 endomyocardial biopsies were evaluated: 31.7% were degree 0, 43.7% 1a and 23.1% 1b. We had only one case of acute clinical rejection confirmed by biopsy as IIIa, and one patient with mediastinitis, both of whom had a good evolution. The mean cyclosporin blood level was 303 Ng/mL. All other parameters also showed a good evolution. CONCLUSION: Generic microemulsion cyclosporin (Sigmasporin Microral®) shows therapeutic efficacy and an excellent bio-safety profile. Its Prescribility is confirmed.